Building the Infrastructure for Value at UCLA. (October 2015) - Clarke, Robin; Hackbarth, Andrew S.; Saigal, Christopher; Skootsky, Samuel A.
<x xml:space="preserve">Abstract</x> Problem Evolving payer and patient expectations have challenged academic health centers (AHCs) to improve the value of clinical care. Traditional quality approaches may be unable to meet this challenge. Approach One AHC, UCLA Health, has implemented a systematic approach to delivery system redesign that emphasizes clinician engagement, a patient-centric scope, and condition-specific, clinician-guided measurement. A physician champion serves as quality officer (QO) for each clinical department/division. Each QO, with support from a central measurement team, has developed customized analytics that use clinical data to define targeted populations and measure care across the full treatment episode. Outcomes From October 2012 through June 2015, the approach developed rapidly. Forty-three QOs are actively redesigning care delivery protocols within their specialties, and 95% of the departments/divisions have received a customized measure report for at least one patient population. As an example of how these analytics promote systematic redesign, the authors discuss how Department of Urology physicians have used these new measures, first, to better understand the relationship between clinical practice and outcomes for patients with benign prostatic hyperplasia and, then, to work toward reducing unwarranted variation. Physicians have received these efforts positively. Early outcome data are encouraging. Next Steps This infrastructure of engaged physicians and targeted measurement is being used to implement systematic care redesign that reliably achieves outcomes that are meaningful to patients and clinicians—incorporating both clinical and cost considerations. QOs are using an approach, for multiple newly launched projects, to identify, test, and implement value-oriented interventions tailored to specific patient populations.